The Determination of The Glycemic Index Preparations Various Sago Papua In Rats (Rattus norvegicus) Induced By Alloxan - Angelica, Wenny (Journal of Food and Life Sciences, 2019)
Several researches had proven that sago have many benefits for several metabolism disorders, one of which is diabetes mellitus (DM). Sago is one of the potential local food as a substitute for rice.The objective of this research was to determine the glycemic index values of sago into three treatments (papeda, sago rice and sago roasted) and determine the decrease in fasting blood glucose level after administration of sago products which was injected into diabetic rats that caused by aloxan injection. This study was prepared in a completely randomized design (RAL) with three replications using 21 rats were divided into 6 groups and 3 rats used in the glycemic index test. Each group was fed a different sago product. These results indicated that the value of glycemic index of sago Papua were sago rice was 50,9 %, papeda was 59,6 % and sago roasted was 64,2 %. Feeding test of papeda, sago rice, and sago roasted made various lowering blood glucose levels of rats that have been induced alloxan.